Analisis Putusan Pengadilan Agama Jambi Tentang Perbuatan Malawan Hukum (PMH) dalam Akad Pembiayaan Murabahah (No.700/Pdt.G/2020/PA.Jmb) - Midia, Suci; Inggrit, Neza Tessya (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2022)
This study aims to analyze the settlement of the case of Unlawful Acts (PMH) in the Murabahah Financing contract contained in Decision Number 700/Pdt.G/2020/PA.Jmb. This research answers three questions. First, how is the dispute resolution in case Number 700/Pdt.G/2020/PA.Jmb regarding unlawful acts (PMH) in the murabahah financing contract. Second, what are the basic considerations of the judge in Court Decision Number 700/Pdt.G/2020/PA.Jmb seen from civil law and sharia economic law. Third, what are the legal consequences of the Jambi Religious Court Decision Number 700/Pdt.G/2020/ PA.Jmb. This research is library research and is a qualitative analysis using the deductive method, the author tries to provide an overview of the case that occurred in decision Number 700/Pdt.G/2020/PA.Jmb. then analyzed to draw conclusions. This study found that the case in the decision was resolved through the ligitation route where the settlement through this ligitation route was carried out at the Jambi Religious Court and in this case the settlement was in accordance with the provisions of absolute competence and the provisions of relative competence regulated in article 141 paragraph (4) RBG, the legal basis used in the settlement of this case is Law Number 7 of 1989 which has been updated with Law Number 50 of 2009, Law Number 21 of 2008, Civil Code, RBG, HIR, and KHES. As for the legal consequences in decision Number 700/Pdt.G/2020/PA.Jmb. namely the Plaintiff is obliged to pay court costs and the Defendant is not charged with legal obligations.